Akibat Hukum terhadap Notaris Menolak Pembuatan Akta Perjanjian Kredit dengan Unsur Riba: Studi di Wilayah Hukum Kota Tuban - Septi Nadila Utami (International Forum of Researchers and Lecturers, 2025)
This thesis examines the legal consequences faced by notaries who refuse to draft credit agreement deeds containing elements of usury, with a focus on Tuban City. The study addresses two main issues: whether a notary can lawfully refuse such a deed, and what legal sanctions may apply if they do. Using a normative legal research approach with case, statutory, and conceptual analyses, the study finds that while the UUJN (Notary Law) does not explicitly permit refusal on religious grounds, it also does not prohibit it if the client can be served by another notary. Refusal based on Islamic principles—specifically the prohibition of usury (riba)—does not warrant sanctions under Article 85 of the UUJN, unless the refusal leads to the client's abandonment. In such cases, administrative sanctions may apply. According to the Notary Code of Ethics, acting outside legal provisions may also result in disciplinary action. The study concludes that current laws do not provide sufficient legal protection for notaries who seek to align their professional duties with religious beliefs. It recommends legal reform to ensure notaries have the right to uphold sharia principles without fear of sanctions, through amendments to the UUJN that consider religious freedom and human rights, while still ensuring client access to legal services.